Harmonisasi Hukum Adat dan Hukum Islam Dalam Sistem Pewarisan Di Semende Provinsi Sumatera Selatan Berasaskan Keseimbangan Sebagai Kontribusi Pembentukan Hukum Kewarisan Nasional - Haidir Rachman (Himmah: Jurnal Kajian Islam Kontemporer, 2019)
Customary inheritance law does not recognize the principle of "legitieme portie" or the absolute part of Islamic inheritance law where inheritance rights have been determined for certain portions of inheritance as stipulated in the Qur'an Surah An-Nisa. The problem of this research is how the harmonization of values and principles in customary inheritance law and Islamic inheritance law in Semende, South Sumatra Province as a contribution to the formation of national inheritance law? The results showed that the harmonization of values and principles in customary inheritance law and Islamic inheritance law in Semende, South Sumatra Province as a contribution to the formation of national inheritance law is that adat can be used as Islamic law, that is, custom in this relationship is a habit in the daily life involved in terms of muamalah (community), not about 'worship.' Because, regarding worship people should not add or subtract what has been determined by Allah as written in the Koran and which has been arranged by the Sunnah of His Apostles as contained in the book Valid Hadiths.